2021
DOI: 10.1212/wnl.0000000000011528
|View full text |Cite
|
Sign up to set email alerts
|

Natural History, Phenotypic Spectrum, and Discriminative Features of Multisystemic RFC1 Disease

Abstract: Objective:To delineate the full phenotypic spectrum, discriminative features, piloting longitudinal progression data, and sample size calculations of RFC1-repeat expansions, recently identified as causing cerebellar ataxia, neuropathy, vestibular areflexia syndrome (CANVAS).Methods:Multimodal RFC1 repeat screening (PCR, southern blot, whole-exome/genome (WES/WGS)-based approaches) combined with cross-sectional and longitudinal deep-phenotyping in (i) cross-European cohort A (70 families) with ≥2 features of CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
161
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(200 citation statements)
references
References 26 publications
11
161
1
9
Order By: Relevance
“…9 CANVAS is worldwide the second most prevalent recessive ataxia after FA. 10 In the Turkish cohort under study, 15 index patients and 3 affected Fm of 202 were found to carry the pathogenic intronic expansion, ranking CANVAS in our cohort at the third position after FA and autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS). Turkish patients with CANVAS presented with a late-onset ataxia and an unexplained dry cough described to begin at young ages.…”
Section: Friedreich's Ataxiamentioning
confidence: 73%
See 3 more Smart Citations
“…9 CANVAS is worldwide the second most prevalent recessive ataxia after FA. 10 In the Turkish cohort under study, 15 index patients and 3 affected Fm of 202 were found to carry the pathogenic intronic expansion, ranking CANVAS in our cohort at the third position after FA and autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS). Turkish patients with CANVAS presented with a late-onset ataxia and an unexplained dry cough described to begin at young ages.…”
Section: Friedreich's Ataxiamentioning
confidence: 73%
“…Turkish patients with CANVAS presented with a late‐onset ataxia and an unexplained dry cough described to begin at young ages. The triad of symptoms, including cerebellar ataxia, neuropathy, and vestibulopathy, was present in eight patients; vestibulopathy was, in the majority of cases, detected after a detailed ear, nose, and throat examination, and thus easily can be missed in routine neurological examination 10 …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It thus fulfills the requirements of primary datasets that can be used to describe natural history progression models and plan treatment trials in almost all of the most frequent ARCAs, including pharmacometric modeling of outcome measures and treatment effects. For example, for RFC1-ataxia, it has helped to reveal multisystemic phenotypes mimicking cerebellar type multiple system atrophy and progressive supranuclear palsy, and hyperkinetic movement disorders such as chorea and dystonia, and provided first sample size calculations based on longitudinal SARA assessments (24). For COQ8A/ADCK3-ataxia, the ARCA Registry facilitated the delineation of clinico-genetic associations, and the longitudinal analysis of SARA scores has provided the first systematic, groupbased evidence for a possible treatment effect of coenzyme Q10 (25).…”
Section: Current Data In the Arca Registrymentioning
confidence: 99%